Agrarian Twilight in Rural West Java: from Accumulation to Exclusion - Tridakusumah, Ahmad Choibar; Soetarto, Endriatmo; Adiwibowo, Soeryo; Wahyuni, Ekawati Sri (Sodality: Jurnal Sosiologi Pedesaan, 2019)
Through this research, the phenomenon of agrarian twilight in rural West java was analyzed by the interactions of agrarian relations, the exclusion process, and actors that involved due to the agrarian history. With the implementation of a critical paradigm by multi method of qualitative research (historical sociology and sociological history) and case study approach, this research releases a deep study of space, temporality and contention so that it can reveal a fundamental problems inequality of agrarian structures in rural West Java from the era colonial up to the present situation. This research was conducted for six months starting from May to October 2018, primary data were collected by in-depth interviews with peasants as key informants of this research and supported by various secondary research data and other relevant documents. The data thereafter analyzed by means of three phases, as interpretative, empirical, and dialectical technique. The results showed that the erosion of the agricultural sector by the industrial and service sectors were complemented by the shrinking of agriculture land due to the conversion of agriculture land to non-agriculture. Historically, agrarian twilight was an alteration from the land accumulation by corporations that further lead to the exclusion of peasants from their land, with the period of time from colonial to the present situation. Unequal access to land, increasing land markets, power, and capital were the triggered. This situations conduced that peasants who directly faced changes in rural agrarian structure were cornered to the most vulnerable position. This condition shows the description of agrarian twilight in rural West Java.